Modulation of Rumen Microbes Through Extracellular Vesicle Released by the Rumen Fluke Calicophoron daubneyi - Allen, Nathan R.; Taylor-Mew, Aspen R.; Wilkinson, Toby J.; Huws, Sharon; Phillips, Helen; Morphew, Russell M.; Brophy, Peter M. (Frontiers in Cellular and Infection Microbiology, 2021)
Parasite derived extracellular vesicles (EVs) have been proposed to play key roles in the establishment and maintenance of infection. Calicophoron daubneyi is a newly emerging parasite of livestock with many aspects of its underpinning biology yet to be resolved. This research is the first in-depth investigation of EVs released by adult C. daubneyi. EVs were successfully isolated using both differential centrifugation and size exclusion chromatography (SEC), and morphologically characterised though transmission electron microscopy (TEM). EV protein components were characterised using a GeLC approach allowing the elucidation of comprehensive proteomic profiles for both their soluble protein cargo and surface membrane bound proteins yielding a total of 378 soluble proteins identified. Notably, EVs contained Sigma-class GST and cathepsin L and B proteases which have previously been described in immune modulation and successful establishment of parasitic flatworm infections. SEC purified C. daubneyi EVs were observed to modulate rumen bacterial populations by likely increasing microbial species diversity via antimicrobial activity. This data indicates EVs released from adult C. daubneyi have a role in establishment within the rumen through the regulation of microbial populations offering new routes to control rumen fluke infection and to develop molecular strategies to improve rumen efficiency.